2019
DOI: 10.3389/fimmu.2019.01750
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Complement System by Pentraxins

Abstract: The functions of pentraxins, like C-reactive protein (CRP), serum amyloid protein P (SAP) and pentraxin-3 (PTX3), are to coordinate spatially and temporally targeted clearance of injured tissue components, to protect against infections and to regulate related inflammation together with the complement system. For this, pentraxins have a dual relationship with the complement system. Initially, after a focused binding to their targets, e.g., exposed phospholipids or cholesterol in the injured tissue area, or micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 85 publications
0
58
0
Order By: Relevance
“…Pentraxin-3 synthesized by neutrophils is mainly stored in neutrophil granules, which can interact with a variety of bacteria, fungi and viruses after release and then propel the phagocytosis and clearance of pathogenic microorganisms [21]. As an important component of innate humoral immunity, pentraxin-3 has the ability to bind complement component C1q and then activate the classical pathway of complement [22,23]. Recently, many studies have showed that pentraxin-3 could modulate in ammatory cells, interact with P-selectin, reduce the nitric oxide (NO) synthesis of endothelial cells, inhibit endothelial cells proliferation and alter their functions, and nally promote vascular in ammatory response and endothelial dysfunction [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Pentraxin-3 synthesized by neutrophils is mainly stored in neutrophil granules, which can interact with a variety of bacteria, fungi and viruses after release and then propel the phagocytosis and clearance of pathogenic microorganisms [21]. As an important component of innate humoral immunity, pentraxin-3 has the ability to bind complement component C1q and then activate the classical pathway of complement [22,23]. Recently, many studies have showed that pentraxin-3 could modulate in ammatory cells, interact with P-selectin, reduce the nitric oxide (NO) synthesis of endothelial cells, inhibit endothelial cells proliferation and alter their functions, and nally promote vascular in ammatory response and endothelial dysfunction [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Pentraxin-3 synthesized by neutrophils is mainly stored in neutrophil granules, which can interact with a variety of bacteria, fungi and viruses after release and then propel the phagocytosis and clearance of pathogenic microorganisms [19]. As an important component of innate humoral immunity, pentraxin-3 has the ability to bind complement component C1q and then activate the classical pathway of complement [20,21]. Recently, many studies have showed that pentraxin-3 could modulate in ammatory cells, interact with P-selectin, reduce the nitric oxide (NO) synthesis of endothelial cells, inhibit endothelial cells proliferation and alter their functions, and nally promote vascular in ammatory response and endothelial dysfunction [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…The following sections focus on pentraxins, particularly the long pentraxin PTX3 (see Ref. [97] for a review on complement regulation by pentraxins).…”
Section: Complement Evasion Strategies Of Aspergillus Fumigatusmentioning
confidence: 99%